Membangunn Organisasi yang Solid dengan Menanamkan Karakter Kader yang Berintegritas dan Bijak di PAC IPNU IPPNU Kepohbaeu - Alif Zahwa Naisya Ariyanto; Meliysa Pasa Bagna Aprilia Said; Muhammad Aiman Hakim; M. Rosyad Efendi; Mawahibul Maulana Syarif (Nawasena Bhakti, 2025)
The socialization activity entitled "Building a Solid Organization by Instilling Integrity and Wisdom in PAC IPNU-IPPNU Kepohbaru Cadres" was initiated in response to internal conflicts within the organization. The purpose of this activity was to raise the participants' critical awareness regarding the importance of professionalism, responsibility, and integrity in fulfilling their roles as future professionals across various fields. The methods used included several stages: the preparation phase, the socialization phase, the implementation phase, and the follow-up phase. The results of the activity indicated a significant increase in participants’ understanding of the material, with post-test scores ranging from 80% to 90% based on data collected via Google Forms. This activity successfully achieved its target, namely to foster collective awareness among cadres regarding the importance of integrity, collective responsibility, and maturity in addressing differences following the election of the new organizational leadership.